Quartz workshop of the Stone Age "Pereboiny" on the Seversky Donets (Rostov region) - Zorov Yu.N.; Kolesnik A.V.; Danilchenko A.Yu. (Cultural Heritage and Modern Technologies)
A new object of archaeological heritage – the Pereboiny quartzite workshop, was identified in the Kamensk district of the Rostov region on the left bank of the Seversky Donets River, on a high root terrace, not far from the famous Kalitvensky quartzite workshops. The workshop is dedicated to the outcrops of quartzite associated with the upper stratum of the bedrock sands of Paleogene age, overlain by whitish sands. The southern and southeastern parts of the monument were destroyed by an old sand quarry. The archaeological material mainly consists of clusters, the largest of which are located in the southern part of the monument, in the talus, and in its southeastern part. A significant number of finds also occur from the territory of the former quarry. The material has been redeposited, has different preservation, and is mainly represented by production waste. There are products of the Middle Paleolithic appearance, as well as of the Late Paleolithic. The Middle Paleolithic component is comparable to products from Kalitvensky quartzite workshops. A significant part of the finds can be attributed to the Neolithic – Eneolithic period. Perhaps the workshop was visited in the Bronze Age. Thus, the open monument was one of the significant production centers of the lower reaches of the Seversky Donets for a very long time.